In vivo induction of neutrophil extracellular traps by Mycobacterium tuberculosis in a guinea pig model. Issue 7 (October 2017) - Filio-Rodríguez, Georgina; Estrada-García, Iris; Arce-Paredes, Patricia; Moreno-Altamirano, María M; Islas-Trujillo, Sergio; Ponce-Regalado, M Dolores; Rojas-Espinosa, Oscar
In 2004, a novel mechanism of cellular death, called 'NETosis', was described in neutrophils. This mechanism, different from necrosis and apoptosis, is characterized by the release of chromatin webs admixed with microbicidal granular proteins and peptides (NETs). NETs trap and kill a variety of microorganisms. Diverse microorganisms, including Mycobacterium tuberculosis, are NET inducers in vitro . The aim of this study was to examine whether M. tuberculosis can also induce NETs in vivo and if the NETs are bactericidal to the microorganism. Guinea pigs were intradermally inoculated with M. tuberculosis H37Rv, and the production of NETs was investigated at several time points thereafter. NETs were detected as early as 30 min post-inoculation and were clearly evident by 4 h post-inoculation. NETs produced in vivo contained DNA, myeloperoxidase, elastase, histones, ROS and acid-fast bacilli. Viable and heat-killed M. tuberculosis, as well as Mycobacterium bovis BCG were efficient NET inducers, as were unilamellar liposomes prepared with lipids from M. tuberculosis . In vitro, guinea pig neutrophils also produced NETs in response to M. tuberculosis . However, neither the in vivo nor the in vitro -produced NETs were able to kill M. tuberculosis. Nevertheless, in vivo, neutrophils might propitiate recruitment and activation of more efficient microbicidal cells.